2024
DOI: 10.1063/5.0191309
|View full text |Cite
|
Sign up to set email alerts
|

Design criteria of load split and chord length ratio for highly loaded compressor tandem cascades

Xiaochen Mao,
Yunyu Wang,
Zhihua Ding
et al.

Abstract: To investigate the design strategy for load split (LS) and chord length ratio (CR) of highly loaded compressor tandem cascades, the parameterization study of the tandem cascades with different LS and CR was carried out. The parameterization results show that the LS is a crucial design parameter that can be used to regulate performance under off-design conditions. Specifically, lower LS enhances performance at positive incidence angles but comes at the cost of degraded performance at negative incidence angles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The results showed that the tandem rotor can break the pressure-rise limit near the stall conditions, thus demonstrating that tandem blade can enhance the efficiency of a highly loaded compressor and expand the stall margin, thereby raising the loading level of axial flow compressors. Mao [11] conducted a parameterization study of highly loaded tandem cascades with different load splits and chord length ratios. The results indicated that load split is a crucial design parameter that can be used to regulate performance under off-design conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the tandem rotor can break the pressure-rise limit near the stall conditions, thus demonstrating that tandem blade can enhance the efficiency of a highly loaded compressor and expand the stall margin, thereby raising the loading level of axial flow compressors. Mao [11] conducted a parameterization study of highly loaded tandem cascades with different load splits and chord length ratios. The results indicated that load split is a crucial design parameter that can be used to regulate performance under off-design conditions.…”
Section: Introductionmentioning
confidence: 99%